The routine use of patient reported outcome measures in healthcare settings. - Dawson, J; Doll, H; Fitzpatrick, R; Jenkinson, C; Carr, A (2010)
The use of patient reported outcome measures might seem to be quite straightforward; however, a number of pitfalls await clinicians with limited expertise. Jill Dawson and colleagues provide a guide for individuals keen to use patient reported outcome measures at a local level.